2003
DOI: 10.1046/j.1468-2982.2003.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Associated with Dialysis: the International Headache Society Criteria Revisited

Abstract: The International Headache Society (IHS) criteria for headache related to haemodialysis consider that the headaches must begin during haemodialysis and terminate within 24 h. Twenty-eight patients whose headaches started by the time they entered the dialysis programme were prospectively studied. We were not able to classify eight patients that presented the headaches between the sessions. Despite the small number of patients in our study being too low to provide a basis for change in the IHS classification, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 12 publications
3
29
1
5
Order By: Relevance
“…A similar percentage was found by Antoniazzi et al [9][10] (62%). However, when only the individuals with HDH were assessed, only 27.3% of them reported their attacks during that period.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…A similar percentage was found by Antoniazzi et al [9][10] (62%). However, when only the individuals with HDH were assessed, only 27.3% of them reported their attacks during that period.…”
supporting
confidence: 89%
“…like Antoniazzi et al 9,10 , the present work also observed patients who reported having had headache attacks between sessions, despite their history of no primary headaches. This finding suggests a possible relationship with the HD, which could allow for classification of such attacks as secondary headaches 10 .…”
supporting
confidence: 77%
See 3 more Smart Citations